Design Build a 4x4 Mimo Microstrip Antenna with Artificial Dielectric Muse Array Technique to increase Antenna Gain pexisting Application 5G - Ade Silvia Handayani; Aan Sugiyanto; Ciksadan Ciksadan; Jon Endri (PROtek : Jurnal Ilmiah Teknik Elektro, 2023)
The development of fifth-generation cellular technology, commonly referred to as "5G" networks, is believed to be able to maximize data speed access needs. In order to maximize the utilization of the existing 5G network in Indonesia, Telkomsel providers are using a frequency of 2.3 GHz with a bandwidth of 50 MHz. So we need an antenna amplifier that is easy to fabricate and place anywhere to maximize the signal capture range. A microstrip antenna is a suitable antenna for this amplifier. The advantage of this antenna is that it has a light mass and is easy to fabricate. while the drawbacks come in the form of narrow bandwidth and small gains. Therefore, an antenna design with an artificial substrate and array technique was made to overcome this. The design of this microstrip antenna was made in the CST Studio Suite 2019. The design was carried out by entering the antenna dimension values to be simulated and seeing the parameters; if they are not suitable, then they need to be optimized again, and when they are appropriate, the design results are fabricated and printed. In testing the signal capture power using the Xirrus WiFi Inspector, this antenna was able to capture the signal beam, which was 105 meters or 40 meters further than not using the antenna. In addition, from testing, it is known that this antenna has a gain of 16.15 dBi. While in the simulation, it is also known that this antenna has the following characteristics: return loss: -32,353 dB (S11), -32,737 dB (S22), -33,974 dB (S33), -34,423 dB (S44), VSWR: 1,049 (VSWR 1), 1,047 (VSWR 2), 1.040 (VSWR 3), 1.038 (VSWR 4), impedance: 50.7 -111 MHz.